Computational and experimental study of swirling ring flow - A. A. Kishkin; Yu. N. Shevchenko; A. A. Zuev; D. A. Zhuikov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In the course of work on the energy perfection of thermal control systems for spacecraft with a twophase circuit, the issue of partial regeneration of thermal energy into electrical energy in a low-speed turbogenerator is considered, part of the design work requires computational modeling during the transport of swirling flows in the axial direction from the external input to the input plane into the impeller, which determines the need for theoretical and experimental elaboration of the problem. The paper considers transformations of equations for changing the amount of fluid motion in boundary conditions of an axial annular channel with fixed cylindrical surfaces. Assuming the symmetry axis of the flows using the integral form of writing the continuity equation, the relations are obtained in the form of two differential equations with expressed derivatives along the channel axis for the total pressure p* and the circumferential velocity constant Cu = UR (const — at the integration step). The equation forms the basis of the algorithm of integration in finite differences supplemented by a system of service equations describing the friction stress, thermodynamic parameters, etc. Test calculations are carried out using real parameters, the results are analyzed.